STRATEGI KREATIF BAHASA IKLAN DI SURAT KABAR - Kurniati, Lisdwiana (JURNAL PESONA, 2016)
The success of advertisement is viewed from the number of changes that appear in the environment or the quantity of product that society need. The categories above are achieved due to the language role as a communication media. The advertisement language in news paper must be able to persuade, and generate people to act and buy the products informed in the news paper. The language should be interesting, effective, logic, well order, and appropriate with the space. The word, phrase, or sentence choosen have to be delivered completely, precisely, and clearly. The success of an advertisement depends on how the selection and the use of word, phrase, and sentence could persuade and generate the reader. Interesting, effectivity of sturcture and meaning, logic, space ordering, and illustration are elements that have to be considered. Keywords: language, creative strategy,and advertisement.